Phosphorus-doped bamboo / wood tar-based carbon material for supercapacitor and preparation method of phosphorus-doped bamboo / wood tar-based carbon material
By pyrolyzing and activating bamboo/wood tar with phytic acid, a phosphorus-doped carbon material is synthesized, addressing low yield and capacitance issues, achieving high carbon yield and superior electrochemical performance.
Patent Information
- Application Number
- CN202411478170.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2024-12-20
AI Technical Summary
Existing methods for preparing carbon materials from biomass oils like bamboo tar result in low carbonization yield and low specific capacitance due to volatile low-boiling point compounds, leading to inefficient supercapacitor performance.
A method involving pyrolysis, vacuum distillation, mixing with phytic acid, high-temperature calcination, and activation to form a phosphorus-doped bamboo/wood tar-based carbon material, enhancing carbon yield and specific capacitance through phenol-phytic acid cross-linking and phosphorus doping.
The method achieves a carbon yield of up to 49% and specific capacitance exceeding 350 F/g, significantly improving electrochemical stability and conductivity compared to previous methods.
Smart Images

Figure CN119160890A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of supercapacitor electrode material preparation, and in particular relates to a method for preparing a phosphorus-doped bamboo / wood tar-based carbon material for a supercapacitor. Background Art
[0002] At present, the use of biomass oils such as bamboo tar to prepare carbon materials still has the problem of low carbonization yield, which is mainly because biomass oil contains a large number of low-boiling point compounds, such as phenols and ketone compounds. These low-boiling point compounds are very volatile during the heating process, resulting in a large loss of biomass oil quality and ultimately a lower carbonization yield. In addition, capacitor carbon prepared from biomass oil still has chemical problems such as low specific capacitance.
[0003] For example, patent CN202011533868.X (publication date: 2021.04.27) uses light fractions of bio-oil as a carbon source to prepare supercapacitor carbon electrodes, but the prepared capacitor carbon has disadvantages such as low specific capacitance, low specific surface area, and low carbon yield. Another example is patent CN110028050A (publication date: 2019.07.19), which mixes bio-oil with a template to obtain a mixture, and then places the mixture in a tubular furnace for carbonization to obtain a supercapacitor carbon material. The supercapacitor material has a low specific surface area and a low carbon yield of only 9.79 to 17.36%.
[0004] The present invention carbonizes and activates the mixture of phytic acid and bamboo / wood tar, and forms phenol-phytic acid cross-linking into a macromolecular structure through COP covalent bonds and the like during the heating process, thereby solidifying volatile light components of bamboo / wood tar, forming more carbon material precursor structures, and greatly improving the carbonization yield and specific capacitance. Summary of the invention
[0005] The technical problem solved by the present invention is to provide a phosphorus-doped bamboo / wood tar-based carbon material for supercapacitors; another technical problem to be solved by the present invention is to provide a preparation method of the phosphorus-doped bamboo / wood tar-based carbon material for supercapacitors.
[0006] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows:
[0007] A method for preparing a phosphorus-doped bamboo / wood tar-based carbon material for supercapacitors comprises the following steps:
[0008] (1) removing water from bamboo / wood tar prepared by pyrolysis of bamboo and wood by vacuum distillation;
[0009] (2) uniformly mixing the distilled bamboo / wood tar and phytic acid, heating and calcining at high temperature to obtain a bamboo / wood pyrolysis tar-based carbonized material;
[0010] (3) mixing and grinding the bamboo / wood pyrolysis tar-based carbonized material and the activator, and then heating the mixture under a nitrogen atmosphere for high-temperature activation;
[0011] (4) washing the product after the reaction with hydrochloric acid and deionized water and then drying it to obtain a phosphorus-doped bamboo / wood pyrolysis tar-based carbon material;
[0012] (5) The phosphorus-doped bamboo / wood pyrolysis tar-based carbon material is ground, mixed with acetylene black and a binder emulsion, and ultrasonically dispersed to obtain a phosphorus-doped bamboo / wood pyrolysis tar-based carbon material for supercapacitors.
[0013] The bamboo wood in step (1) includes hardwood, softwood or bamboo.
[0014] The pyrolysis temperature in step (1) is 200-600°C.
[0015] In the step (2), the mass ratio of phytic acid to bamboo / wood tar is 0.2:1-1.
[0016] The temperature of high temperature calcination in step (2) is 400-600°C.
[0017] In the step (3), the mass ratio of the activator to the bamboo / wood tar-based carbonized material is 1-2:1; the mass ratio of the phosphorus-doped bamboo / wood pyrolysis tar-based carbon material, acetylene black and adhesive emulsion is 8:1:1, and the concentration of the adhesive emulsion is 60%.
[0018] In the step (3), the activator is any one of sodium amide, potassium hydroxide, potassium carbonate, potassium oxalate, sodium carbonate or sodium hydroxide.
[0019] The temperature of high temperature activation in step (3) is 600-800°C.
[0020] In the step (4), the adhesive is PTFE, PVDF or PMM.
[0021] The method for preparing the phosphorus-doped bamboo / wood tar-based carbon material for supercapacitors prepares the phosphorus-doped bamboo / wood tar-based carbon material.
[0022] Compared with the prior art, the present invention has the following advantages:
[0023] (1) The present invention successfully synthesized phosphorus-doped bamboo / wood tar charcoal materials by carbonizing and activating bamboo / wood tar and plant mixtures. Compared with other biomass tar charcoal materials in the past, the prepared charcoal materials not only showed higher specific capacitance and excellent electrochemical stability, but also had a higher carbon yield (>40%). This invention can turn bamboo / wood tar into treasure, realize the high-value utilization of bamboo / wood tar, and improve economic benefits.
[0024] (2) The carbonization activation of bamboo / wood tar and phytic acid used in the present invention is equivalent to the introduction of P element (provided by phytic acid), which not only improves the carbon yield, but also improves the electrochemical performance. The method is simple and convenient and can be applied on a large scale. The prepared phosphorus-doped carbon material has a carbon yield of up to 49%, which is higher than the yield of 9.79-17.36% of the carbon material of patent CN110028050A, and has good economic benefits. At the same time, phosphorus doping improves the conductivity and charge transfer ability of the material, and the mass specific capacitance of the material (>350F / g at 1A / g current density) is also much higher than the supercapacitor carbon material prepared from current wood fiber raw materials (>350F / g at 1A / g current density). BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 GCD curves of the phosphorus-doped bamboo / wood tar-based carbon material for supercapacitors prepared in Example 1 of the present invention at different scanning speeds;
[0026] Figure 2 CV curves of the phosphorus-doped bamboo / wood tar-based carbon material for supercapacitors prepared in Example 1 of the present invention at different current densities;
[0027] Figure 3 This is a rate characteristic diagram of the phosphorus-doped bamboo / wood tar-based carbon material for supercapacitors prepared in Example 1 of the present invention;
[0028] Figure 4 This is an EIS impedance graph of the phosphorus-doped bamboo / wood tar-based carbon material for supercapacitors prepared in Example 1 of the present invention;
[0029] Figure 5 This is an infrared spectrum of a mixture of bamboo / wood tar and phytic acid in the phosphorus-doped bamboo / wood tar-based carbon material for supercapacitors prepared in Example 2 of the present invention during the heating process. DETAILED DESCRIPTION
[0030] The present invention is further illustrated below in conjunction with specific examples. The examples are implemented based on the technical solutions of the present invention. It should be understood that these examples are only used to illustrate the present invention and are not used to limit the scope of the present invention.
[0031] Example 1
[0032] (1) Pyrolyzing bamboo at 400°C for 2 h, and distilling the obtained bamboo tar under reduced pressure at 50°C to remove moisture;
[0033] (2) taking 10 g of the distilled bamboo tar and 2 g of phytic acid, mixing them evenly in a crucible, and calcining them at 450° C. for 2 h to obtain a carbonized material;
[0034] (3) Take 1 g of carbonized material and 1 g of sodium amide and mix them thoroughly, put them into a tube furnace, and calcine them at 600° C. for 2 h in a nitrogen atmosphere;
[0035] (4) The product after the reaction is washed with hydrochloric acid and deionized water, and then dried at 100° C. to obtain a carbon material.
[0036] Example 2
[0037] (1) Pyrolyzing bamboo at 400°C for 2 h, and distilling the obtained bamboo tar under reduced pressure at 50°C to remove moisture;
[0038] (2) taking 10 g of the distilled bamboo tar and 10 g of phytic acid and mixing them evenly in a crucible, and calcining them at 450° C. for 2 h to obtain a carbonized material;
[0039] (3) Take 1 g of carbonized material and 1 g of sodium amide and mix them thoroughly, put them into a tube furnace, and calcine them at 600° C. for 2 h in a nitrogen atmosphere;
[0040] (4) The product after the reaction is washed with hydrochloric acid and deionized water, and then dried at 100° C. to obtain a carbon material.
[0041] Comparative Example 1
[0042] (1) Pyrolyzing bamboo at 400°C for 2 h, and distilling the obtained bamboo tar under reduced pressure at 50°C to remove moisture;
[0043] (2) taking 10 g of the distilled bamboo tar into a crucible and calcining it at 450° C. for 2 h to obtain a carbonized material;
[0044] (3) Take 1 g of carbonized material and 1 g of sodium amide and mix them thoroughly, put them into a tube furnace, and calcine them at 600° C. for 2 h in a nitrogen atmosphere;
[0045] (4) The product after the reaction is washed with hydrochloric acid and deionized water, and then dried at 100° C. to obtain a carbon material.
[0046] Example 3
[0047] (1) Pyrolyze apple wood at 400°C for 2 h, and distill the resulting wood tar under reduced pressure at 50°C to remove moisture;
[0048] (2) taking 10 g of the distilled wood tar into a crucible and calcining it at 450° C. for 2 h to obtain a carbonized material;
[0049] (3) Take 1 g of carbonized material and 1 g of sodium amide and mix them thoroughly, put them into a tube furnace, and calcine them at 600° C. for 2 h in a nitrogen atmosphere;
[0050] (4) The product after the reaction is washed with hydrochloric acid and deionized water, and then dried at 100° C. to obtain a carbon material.
[0051] Example 4
[0052] (1) Pyrolyzing bamboo at 400°C for 2 h, and distilling the obtained bamboo tar under reduced pressure at 50°C to remove moisture;
[0053] (2) taking 10 g of the distilled bamboo tar into a crucible and calcining it at 450° C. for 2 h to obtain a carbonized material;
[0054] (3) Take 1 g of the carbonized material and mix it thoroughly with 2 g of sodium amide, put it into a tube furnace, and calcine it at 600°C for 2 h in a nitrogen atmosphere;
[0055] (4) The product after the reaction is washed with hydrochloric acid and deionized water, and then dried at 100° C. to obtain a carbon material.
[0056] Example 5
[0057] (1) Pyrolyzing bamboo at 400°C for 2 h, and distilling the obtained bamboo tar under reduced pressure at 50°C to remove moisture;
[0058] (2) taking 10 g of the distilled bamboo tar into a crucible and calcining it at 450° C. for 2 h to obtain a carbonized material;
[0059] (3) 1 g of the carbonized material was mixed with 2 g of potassium hydroxide, placed in a tube furnace, and calcined at 800° C. for 2 h in a nitrogen atmosphere;
[0060] (4) The product after the reaction is washed with hydrochloric acid and deionized water, and then dried at 100° C. to obtain a carbon material.
[0061] Example 6
[0062] (1) Pyrolyzing bamboo at 400°C for 2 h, and distilling the obtained bamboo tar under reduced pressure at 50°C to remove moisture;
[0063] (2) taking 10 g of the distilled bamboo tar into a crucible and calcining it at 450° C. for 2 h to obtain a carbonized material;
[0064] (3) Take 1 g of the carbonized material and mix it thoroughly with 2 g of sodium amide, put it into a tube furnace, and calcine it at 700°C for 2 h in a nitrogen atmosphere;
[0065] (4) The product after the reaction is washed with hydrochloric acid and deionized water, and then dried at 100° C. to obtain a carbon material.
[0066] Performance characterization:
[0067] Depend on Figure 5It can be seen that the mixture of bamboo / wood tar and phytic acid at 100℃ has a -1 The stretching vibration peak of the phosphorus-oxygen bond appears at 800-1000cm -1 The bending vibration of phosphorus-oxygen bond appeared at , and a new peak was generated, which indicated that the bamboo / wood tar and phytic acid mixture was cross-linked during the heating process, fixing the light components in the bamboo tar.
[0068] Electrochemical performance test:
[0069] The sample carbons of Examples 1 to 6 and Comparative Example 1 were used as electrode materials, and the electrochemical properties of the carbon materials were detected on an electrochemical workstation, including cyclic voltammetry (CV), constant current charge and discharge (GCD) and electrochemical impedance spectroscopy (EIS): mercury-mercuric oxide was selected as the reference electrode, a platinum mesh was used as the counter electrode, and the sample carbon material was coated on nickel foam as the working electrode, which was connected to the test system through an electrode clamp, and 6 mol / L KOH was used as the electrolyte, and the measurement was performed on a Shanghai Chenhua CHI660E electrochemical workstation.
[0070] The specific operation is as follows: Cleaning the nickel foam: trim the nickel foam to a size of 1cm×5cm and put it into a glass container. First, add acetone for ultrasonic cleaning for 30 minutes; secondly, use 3mol / L hydrochloric acid for ultrasonic cleaning for 15 minutes, and finally bake it at 65°C in a vacuum drying oven for 24 hours to obtain clean nickel foam.
[0071] Sample coating: Weigh 8 mg of sample carbon, 1 mg of conductive agent acetylene black and 1 mg of adhesive polytetrafluoroethylene and add them into a 2 mL centrifuge tube, then put them into an ultrasonic cleaner for ultrasonic dispersion to obtain phosphorus-doped bamboo / wood tar-based carbon materials for supercapacitors. Finally, coat the electrode material on nickel foam with a coating mass of 1 to 2 mg. 2 The nickel foam was coated and then transferred to a vacuum drying oven at 65°C for 24 hours. The dried nickel foam was pressed into sheets and kept at a pressure of 10 MPa for 10 to 15 seconds. The nickel foam was weighed again to calculate the mass difference between the nickel foam before and after coating. The actual mass was further calculated and applied to the electrochemical property test.
[0072] The nickel foam coated with electrode material was used as the working electrode, the Hg / HgO reference electrode and the Pt mesh counter electrode were inserted into a 6 mol / L potassium hydroxide electrolyte through a three-hole electrode holder. In the Cyclic Voltammetry mode, an electrochemical workstation was used to test the parameters in the voltage range of -1 to 0 V, and the voltage scan rates were 5, 10, 20, 50, and 100 mV / s, respectively. The cyclic voltammetry curve (CV) was measured; in the Chronopotentiometry mode, the constant current charge-discharge diagram (GCD) was measured, and the test current density was 0.5, 1, 5, 10, and 20 A / g, respectively. Figure 3 As shown; in the AC Impedance mode, the frequency parameter range is 0.01 Hz to 100 kHz, and the electrochemical impedance spectroscopy (EIS) is measured.
[0073] Table 1 Comparison table of physical and chemical indicators of carbon materials
[0074] sample Carbonization rate / % Specific capacitance F / g Example 1 35.8 350 Example 2 49.1 165 Comparative Example 1 17.9 301 Example 3 18.1 320 Example 4 18.2 290 Example 5 17.5 340 Example 6 17.9 280
[0075] It can be seen from Table 1 that the prepared samples all have relatively good mass specific capacitance, among which the mass specific capacitance of Example 1 is the largest.
[0076] Example 1: Electrochemical test. Figure 1 , Figure 2 The cyclic voltammogram and constant current charge-discharge diagram of Example 1; Figure 3 The rate characteristic of Example 1 is 68.2%. From the CV curve, it can be seen that as the scan rate increases, the scan area gradually increases. When the scan rate reaches 100mV / s, the scan area is the largest and maintains a rectangular structure, indicating good electrochemical performance. From the EIS, it can be seen that the slope of the curve is large and the intersection of the horizontal axis is small, indicating that the material has a small internal resistance and diffusion resistance. Figure 4 It is observed in the illustration that it has a smaller semicircle, indicating that the prepared electrode material has a smaller contact resistance in the electrolyte. In the GCD diagram, it can be seen that the charge and discharge time is the longest when the current density is 0.5A / g, and the specific capacitance is the largest at 376F / g and maintains a highly symmetrical shape. The rate characteristic diagram shows that the prepared electrode material still maintains good charge and discharge performance at high current density.
[0077] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing phosphorus-doped bamboo / wood tar-based carbon materials for supercapacitors, Features: The following steps are involved: (1) removing water from bamboo / wood tar obtained by pyrolysis of bamboo and wood by vacuum distillation; (2) uniformly mixing the distilled bamboo / wood tar and phytic acid, heating and calcining at high temperature to obtain a bamboo / wood pyrolysis tar-based carbonized material; (3) mixing and grinding the bamboo / wood pyrolysis tar-based carbonized material and the activator, and then heating the mixture under a nitrogen atmosphere for high-temperature activation; (4) washing the product after the reaction with hydrochloric acid and deionized water and then drying it to obtain a phosphorus-doped bamboo / wood pyrolysis tar-based carbon material; (5) The phosphorus-doped bamboo / wood pyrolysis tar-based carbon material is ground, mixed with acetylene black and a binder emulsion, and ultrasonically dispersed to obtain a phosphorus-doped bamboo / wood pyrolysis tar-based carbon material for supercapacitors.
2. The method for preparing phosphorus-doped bamboo / wood tar-based carbon material for supercapacitors according to claim 1, Features: The bamboo wood in step (1) includes hardwood, softwood or bamboo.
3. The method for preparing phosphorus-doped bamboo / wood tar-based carbon material for supercapacitors according to claim 1, Features: The pyrolysis temperature in step (1) is 200-600°C.
4. The method for preparing phosphorus-doped bamboo / wood tar-based carbon material for supercapacitors according to claim 1, Features: In the step (2), the mass ratio of phytic acid to bamboo / wood tar is 0.2:1-1.
5. The method for preparing phosphorus-doped bamboo / wood tar-based carbon material for supercapacitors according to claim 1, Features: The temperature of high temperature calcination in step (2) is 400-600°C.
6. The method for preparing phosphorus-doped bamboo / wood tar-based carbon material for supercapacitors according to claim 1, Features: In the step (3), the mass ratio of the activator to the bamboo / wood tar-based carbonized material is 1-2:1; the mass ratio of the phosphorus-doped bamboo / wood pyrolysis tar-based carbon material, acetylene black and adhesive emulsion is 8:1:1, and the concentration of the adhesive emulsion is 60%.
7. The method for preparing phosphorus-doped bamboo / wood tar-based carbon material for supercapacitors according to claim 1, Features: In the step (3), the activator is any one of sodium amide, potassium hydroxide, potassium carbonate, potassium oxalate, sodium carbonate or sodium hydroxide.
8. The method for preparing phosphorus-doped bamboo / wood tar-based carbon material for supercapacitors according to claim 1, Features: The temperature of high temperature activation in step (3) is 600-800°C.
9. The method for preparing phosphorus-doped bamboo / wood tar-based carbon material for supercapacitors according to claim 1, Features: In the step (5), the adhesive is PTFE, PVDF or PMM.
10. The method for preparing a phosphorus-doped bamboo / wood tar-based carbon material for supercapacitors according to any one of claims 1 to 9, wherein the phosphorus-doped bamboo / wood tar-based carbon material is prepared.
Citation Information
Patent Citations
Method for preparing supercapacitor carbon material by adopting bio-oil
CN110028050A
Bio-oil light fraction-based bread-shaped porous activated carbon as well as preparation method and application thereof
CN112713005A
Cited By
Bamboo biomass carbon material with low Si content as well as preparation method and application of bamboo biomass carbon material
CN119929795A
